Ability to provide and request emotional support in affective relationships, in accordance with attachment profiles - Gómez Zapiain, Javier; Ortiz, María José; Gómez Lope, Julen (Anales de Psicología / Annals of Psychology, 2012)
The aim of this study was to analyze gender differences in the ability to provide (support position) and request (dependence position) emotional support in affective relationships, in accordance with attachment profiles. These abilities were analyzed, as they are considered to form part of the caregiving system within couple relationships. The aim was to determine the extent to which these abilities depend on gender contents attributed to the sex variable or to attachment profiles. Hundred and twenty five women and men, aged between 22 and 65 participated in this study, who at the time of research had a stable couple relationship. Results obtained confirmed that tendency to avoidance interfered in support and dependency abilities, in both, men and women. Anxiety, however, was modulated by gender, as significant differences were found between women and men in the studied variables. This study provides evidence about the importance of combining anxiety and avoidance variables to obtain groups that represent attachment categories. Analysis with categories clarified notably previous results, as it was found that highly anxious men provided care as much as women, as long as avoid- ance levels were low. Nevertheless, in the anxious women group, high levels of avoidance did not inhibit caregiving. Results from this study suggest the need of studying more the psychological features of the avoidant-fearful profile, formed by people with high scores in anxiety and avoidance.